Big data analytics for summit group hospital using enterprise architecture as strategic approach / Kholijah Norbib, Nur Nesa Nashuha Ismail, Nur Azaliah Abu Bakar and Surya Sumarni Hussein - Norbib, Kholijah; Nashuha, Nur Nesa; Abu Bakar, Nur Azaliah; Hussein, Surya Sumarni (Universiti Teknologi MARA, 2022)
Healthcare is known for being a highly intensive engagement with a complex organisation, and it involves numerous levels of stakeholders. A big data analytics solution is required to simplify and improve the process's overall data efficacy and flow. However, there are many challenges in implementing big data analytics in a healthcare organisation, as evidenced in some situations. The difficulties that must be addressed are high costs, time-consuming processes in establishing strategic management, and becoming a patient-centred organisation with optimal coordination. As a result, certain studies that have been conducted are suggested a feasible approach for big data analytics is by implementing Enterprise Architecture (EA) in health organisations. The TOGAF ADM model has been chosen as the methodology for implementing EA in a healthcare organisation due to the power of its flexible methods in merging artefacts and its focus on processes. When adopting EA, four architecture layers are examined: Business, Data, Application, and Technology (BDAT). The problems and As-Is environment have been explored, implying that healthcare organisations require EA to assure continuous service delivery. Significantly, the proposed approach will aid stakeholders in quickly adopting the business transformation through the use of EA.